EFL students’ perception toward Free4talk in enhancing speaking ability - Sarah Davina L Tobing; Emeliya Sukma Dara Damanik (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2025)
This research investigates how EFL students utilize Free4Talk to improve their English-speaking abilities. A significant number of EFL learners face challenges related to anxiety and self-doubt, which can impede successful communication. Free4Talk offers a flexible and nurturing atmosphere where students can engage with both native and non-native speakers. Adopting a phenomenological approach, this research gathered data through semi-structured interviews to explore students’ experiences. The results show that students view Free4Talk favorably, noting enhanced self-confidence and better speaking skills. They value the supportive environment and constructive feedback, which promotes ongoing practice. Although there are obstacles like technical difficulties, students suggest implementing a more organized approach to fully harness Free4Talk's advantages. In summary, this research emphasizes Free4Talk's effectiveness in enhancing the speaking skills of EFL students and highlights the vital role of positive perceptions of educational technology in influencing learning outcomes.